Tanda-tanda Zaman Pada Perubahan Iklim Dan Dampaknya Pada Dunia - Helvin Murni Gulo; Aprianus Ledrik Moimau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This article talks about the signs of the times on climate change and its impact on the world. The purpose of this study is to explore people's perceptions of environmental conditions related to climate and symptoms of changes that occur. Climate change has become a major focus globally because of its increasingly pronounced impact on various aspects around the world. Signs of the times on climate change are a major concern in assessing its environmental, economic, and social impacts. Understand the impact of known climate change symptoms on coastal environments and identify ways of adaptation by communities in the face of climate change that has an impact on these economic activities. The results showed that the symptoms of climate change and its impact have been felt by the community. Although they do not understand that the shift in the time of the transition of seasons, namely the rainy season, that is, the dry season is a symptom of climate change. Perceived impact